2022
DOI: 10.1057/s41311-022-00381-0
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and US foreign policy: key debates and new findings

Abstract: Polarization in the USA has been on the rise for several decades. In this context, few observers expect politics today to stop “at the water’s edge,” as the old cliché goes. But key questions about the relationship between polarization and US foreign policy remain to be fully answered. To what extent are American ideas about foreign policy now polarized along partisan lines? How is polarization changing the foreign policy behavior of the US Congress and President? And how is polarization altering the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 114 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The argument builds on the assumption that public attitudes towards foreign policy can impact decision-makers. It is, however, a highly questionable assumption, as many surveys show that foreign policy issues figure low on the priorities of most voters (Foyle, 2017;Friedrichs & Tama, 2022). Thus, the focus in this section shifts from strategic culture as a main explanatory factor to the potential significance of state-society relations and domestic government institutions.…”
Section: The Threats To Liberal Interventionism Come From Within the ...mentioning
confidence: 97%
“…The argument builds on the assumption that public attitudes towards foreign policy can impact decision-makers. It is, however, a highly questionable assumption, as many surveys show that foreign policy issues figure low on the priorities of most voters (Foyle, 2017;Friedrichs & Tama, 2022). Thus, the focus in this section shifts from strategic culture as a main explanatory factor to the potential significance of state-society relations and domestic government institutions.…”
Section: The Threats To Liberal Interventionism Come From Within the ...mentioning
confidence: 97%
“…20 When it comes to the consequences of polarization, research has suggested that "polarization is making it harder for the US to contribute constructively to global problem-solving and international order maintenance." 21 Virtually all existing scholarly work on polarization and US foreign policy has been implicitly or explicitly rationalist in orientation. There is, however, a particular version of constructivism that may help advance our understanding of how societal polarization carries over into the realm of foreign and security policy.…”
Section: Domestic Polarization and Us Foreign Policymentioning
confidence: 99%
“…Legislative polarization also risks policy gridlock, including on foreign policy issues. For example, this poses a significant problem if Congress needs to affirmatively approve line items for Israel aid in the budget (Friedrichs and Tama 2022).…”
Section: Cost Of Us Backlashmentioning
confidence: 99%
“…Legislative polarization also risks policy gridlock, including on foreign policy issues. For example, this poses a significant problem if Congress needs to affirmatively approve line items for Israel aid in the budget (Friedrichs and Tama 2022). By alienating Democrats and invoking these costs, the speech could serve as a meaningful signal to the Israeli public about Netanyahu's preferences.…”
Section: Mr Netanyahu Goes To Washingtonmentioning
confidence: 99%